Aplication of the TikTok Assisted Problem-Based Learning Model on Straight-Line Equations : Penerapan Model Pembelajaran Problem Based Learning Berbantuan Aplikasi Tiktok pada Materi Persamaan Garis Lurus - Dian Fitra; Desyanti Br Sinaga (Borneo Educational Journal (Borju), 2023)
This study aims to see how the application of the problem-based learning model was assisted by the TikTok application on straight-line equations. This research was qualitative research using a descriptive approach. The subjects in this study were 19 class VIII-I students of SMPN 9 Bayung Lencir. The data obtained in this study were analyzed through several stages, namely reducing data, presenting data, and verifying data or drawing conclusions. The research instruments used were tests and interviews. The results of the study show that students enjoy participating in the learning process using the problem-based learning model and learning videos using the TikTok application. The results of the interviews concluded that students felt happy and enthusiastic about learning straight-line equations material because the application of problem-based learning models and learning videos using the TikTok application was their first experience and was a pleasant experience. In addition, the advantage of using learning videos using the TikTok application is that learning videos can be played back anytime and anywhere so students find it helpful when they want to repeat learning material. Furthermore, the results of observations made by the teacher concluded that the use of video learning based on the TikTok application was able to make students more focused, and more active and students were not sleepy during the learning process